Patterns of care and the survival of elderly patients with high-risk endometrial cancer: A case-control study from the FRANCOGYN group. Issue 11 (November 2017) - Rousselin, A.; Bendifallah, S.; Nyangoh Timoh, K.; Ouldamer, L.; Canlorbe, G.; Raimond, E.; Hudry, N.; Coutant, C.; Graesslin, O.; Touboul, C.; Collinet, P.; Bricou, A.; et al.
Abstract: Background: The standard of care of endometrial cancer involves complex procedures such as pelvic and para-aortic lymphadenectomy and omentectomy, particularly for high-risk endometrial cancer. Few data are available about these complex surgical procedures and adjuvant therapy in elderly women. We aim to examine treatment and survival of elderly women diagnosed with high-risk endometrial cancer. Study design: We performed a case-control study of women diagnosed between 2001 and 2013 with high-risk endometrial cancers. Women older than 70 years (n = 198) were compared with patients <70 years (n = 198) after matching on high-risk for recurrence and LVSI status. Results: Elderly patients had lymphadenectomies less frequently compared with younger patients (76% vs 96%, p < 0.001) and no adjuvant treatment more frequently (17% vs 8%, p = 0.005) due to less chemotherapy being administered (23% vs 46%, p < 0.001). The 3-year DFS, CSS and OS of patients ≥70 years was 52% (43–61), 81% (74–88) and 61% (53–70), respectively. These were significantly lower than the 3-year DFS, CSS, and OS of younger patients, which was 75% (68–82) (p < 0.001), 92% (87–96) (p < 0.008) and 75% (69–82) (p = 0.018), respectively. Cox proportional hazard models found that elderly women had 57% increased risk of recurrence (hazard ratio 1.57, 95% CI 1.04–2.39) compared with younger patients. Conclusion: Although we found an independently significant lower DFS in elderly patients with high-risk endometrial cancer when compared with young patients, elderly women are less likely to be treated with lymphadenectomy and chemotherapy. Specific guidelines for management of elderly patients with high-risk endometrial cancer are required to improve their prognosis.